Eukaryotic ribosome assembly - Baßler, Jochen; Hurt, Ed (Annual review of biochemistry, 2019)
Ribosomes, which synthesize the proteins of a cell, comprise ribosomal RNA and ribosomal proteins, which coassemble hierarchically during a process termed ribosome biogenesis. Historically, biochemical and molecular biology approaches have revealed how preribosomal particles form and mature in consecutive steps, starting in the nucleolus and terminating after nuclear export into the cytoplasm. However, only recently, due to the revolution in cryo-electron microscopy, could pseudoatomic structures of different preribosomal particles be obtained. Together with in vitro maturation assays, these findings shed light on how nascent ribosomes progress stepwise along a dynamic biogenesis pathway. Preribosomes assemble gradually, chaperoned by a myriad of assembly factors and small nucleolar RNAs, before they reach maturity and enter translation. This information will lead to a better understanding of how ribosome synthesis is linked to other cellular pathways in humans and how it can cause diseases, including cancer, if disturbed.